Pengaruh Pupuk NPK dan Pupuk Organik terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Main Nursery - Adnan, Indah Safitri; Utoyo, Bambang; Kusumastuti, Any (Politeknik Negeri Lampung, 2015)
NPK fertilizer and organic fertilizer on the growth of oil palm seedlings in the main nursery aims to determine a single effect or interaction between the two on the growth of oil palm seedlings in the main nursery. The experiment was conducted at the Polytechnic of Lampung from July 2013 to March 2014. The study used Complete Randomized Design (CRD) factorial, which consists of two factors and each combination was repeated 3 times. The first factor of NPK fertilizer with 3 levels, 100%, 50%, and 25% of the dose recommendation as much as 142 g. The second factor is the dose of organic fertilizer (Organonitrofos) with 3 levels of treatment, without organic fertilizer, 18 g polybag-1, and 36 g polybag-1. Observation variables such as plant height, number of midrib, stem diameter, length of midrib, shoot dry weight, root dry weight and P total. The results showed that NPK fertilizer at the age of 9 months to increase the length midrib, shoot dry weight and root dry weight. Effect of dosage of the best there is at 100%. The combination of NPK fertilizer and organic fertilizer there is an interaction of the dry weight of the roots and the best interaction was achieved by treatment of 50% NPK fertilizer and organic fertilizer 36 g polybag-1.Keywords: NPK fertilizer, oil palm, organonitrofosPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/20